Effects of Nicorandil on the cAMP-Dependent Cl− Current in Guinea-Pig Ventricular Cells - Nami Nishimura; Yoshie Reien; Akio Matsumoto; Takehiko Ogura; Yuuichi Miyata; Kazumasa Suzuki; Yuji Nakazato; Hiroyuki Daida; Haruaki Nakaya (Elsevier, 2010)
In guinea-pig cardiomyocytes, a cAMP-dependent Cl− current (ICl,cAMP) flows through a cardiac isoform of the cystic fibrosis transmembrane conductance regulator (CFTR), which belongs to a family of the ATP-binding cassette (ABC) proteins. Although several K+-channel openers and sulfonylurea ATP-sensitive K+ (KATP)-channel blockers reportedly inhibit ICl,cAMP, effects of nicorandil on the Cl− current have not been evaluated. This study was conducted to examine the effects of nicorandil on ICl,cAMP in isolated guinea-pig ventricular cells using patch clamp techniques. Nicorandil in concentrations higher than 300 μM enhanced the ICl,cAMP preactivated by 0.1 μM isoproterenol. The isoproterenol-induced ICl,cAMP was inhibited by 100 μM glibenclamide, but not by 100 μM pinacidil. SNAP (S-nitroso-N-acetyl-d,l-penicillamine, 10 μM), a nitric oxide (NO) donor, similarly enhanced the isoproterenol-induced ICl,cAMP. However, SG-86, a denitrated metabolite possessing K+ channel-opening action, failed to enhance the Cl− current. When the ICl,cAMP was activated by 3-isobutyl-1-methylxanthine (IBMX, 30 μM), either nicorandil or SNAP failed to enhance the isoproterenol-induced ICl,cAMP. Thus, nicorandil enhances ICl,cAMP in guinea-pig cardiomyocytes through an increase in intracellular cGMP, although direct modulation of ICl,cAMP by NO cannot be completely excluded. Keywords:: cAMP-dependent Cl− current, nicorandil, heart, nitric oxide (NO), cGMP